The Role of Academic Motivation in Predicting Turkish Undergraduates’ Life Satisfaction and Academic Procrastination - GÜDÜL, MERYEM DEMİR; Can, Gürhan; Ceyhan, Aydoğan Aykut (Turkish Psychological Counseling and Guidance Association, 2021)
The present study aims to determine the motivational profiles of university students through a person-centered approach and to examine the relationship between motivational profiles, academic procrastination, and life satisfaction. The study participants comprised 1,770 undergraduates (1019 female, 749 male, and 2 not specified), who were categorized into three main profiles: (a) students with high levels of both intrinsic and extrinsic motivation but with a low level of amotivation (33.8%), those with a "high-level academic motivation profile"; (b) students with moderate levels of both intrinsic and extrinsic motivation but with low levels of amotivation (44.9%), those with a "medium-level academic motivation profile"; and (c) students with low levels of both intrinsic and extrinsic motivation with high levels of amotivation (21.3%), those with a "low-level academic motivation profile. The results of this study revealed that students with a high-level academic motivation profile have a high level of life satisfaction and a low level of academic procrastination. The results also show that students with medium-level academic motivation profiles have higher levels of life satisfaction than students with low-level academic motivation profiles. However, the academic procrastination level of students with medium-level academic motivation was found to be lower than that of students with a low-level academic motivation profile. © Common Ground Research Networks, Lindsay Asquith, Sumati Ahuja, All Rights Reserved.
Türk Üniversite Öğrencilerinin Yaşam Doyumları ve Akademik Ertelemelerini Belirlemede Akademik Motivasyonun Rolü
Keywords: Academic Motivation; Motivational Profiles; Self-Determination Theory; Academic Procrastination; Life Satisfaction